Inklusi Keuangan dalam Pengentasan Kemiskinan di Wilayah Kepulauan: Studi Kasus Provinsi Kepulauan Riau - Yohanes Eki Apriliawan (Jurnal Archipelago, 2025)
This research examines the importance of accessibility to financial infrastructure in efforts to alleviate poverty in the archipelagic region of the Riau Islands Province. The geographical condition consisting of numerous islands poses unique challenges in providing equitable access to financial services. Utilizing the Spatial Error Model and granular data down to the village/sub-district level, this study finds that the number of Banks and the presence of Automatic Teller Machines have a significant influence on the Global Relative Deprivation Index (GRDI) of poverty. The more Banks and ATMs in an area, the lower the poverty level tends to be. However, the accessibility of financial infrastructure in the Riau Islands is still uneven, especially in rural areas that have higher poverty rates. Therefore, the recommended policy measures include expanding Bank networks and placing ATMs in rural areas, innovating financial services tailored to the archipelagic conditions, improving financial literacy and inclusion among the community, developing digital finance, as well as improving inter-island transportation infrastructure. These recommendations are expected to broaden access to financial services and contribute to poverty alleviation efforts in Riau Islands Province.